Professional growth in adaptive teaching competence as a result of Lesson Study. (November 2017) - Schipper, Tijmen; Goei, Sui Lin; de Vries, Siebrich; van Veen, Klaas
Abstract: Since classrooms have become more diverse, professional development on adaptive teaching seems critically important, yet turns out to be complex. Lesson Study may address this issue due to its explicit focus on student learning. In total, 22 Lesson Study participants from different school contexts were interviewed. Clarke and Hollingsworth's Interconnected Model of Professional Growth was used as the analyzing framework to explore its adequacy for understanding teacher professional growth. The results reveal teacher professional growth in adaptive teaching competence and show how the intensive focus on student learning, collaborative professional experimentation and the facilitators' role may contribute to this. Highlights: Suggests the potential of Lesson Study to promote adaptive teaching competence. Approaches Lesson Study as a means to stimulate teacher professional growth. Stresses and clarifies the importance of appropriate school conditions in Lesson Study practice. Proposes a model for teacher professional growth in the context of Lesson Study.